2008
DOI: 10.1128/aac.00761-07
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Antiretroviral Regimens Containing Tenofovir Disoproxil Fumarate and Atazanavir-Ritonavir in Adolescents and Young Adults with Human Immunodeficiency Virus Infection

Abstract: The primary objective of this study was to measure atazanavir-ritonavir and tenofovir pharmacokinetics when the drugs were used in combination in young adults with human immunodeficiency virus (HIV). HIV-infected subjects >18 to <25 years old receiving (>28 days) 300/100 mg atazanavir-ritonavir plus 300 mg tenofovir disoproxil fumarate (TDF) plus one or more other nucleoside analogs underwent intensive 24-h pharmacokinetic studies following a light meal. Peripheral blood mononuclear cells were obtained at 1, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
4
36
1
1
Order By: Relevance
“…In contrast, we found that the GMs (90% CI) for tenofovir AUC and C min in the presence of atazanavir-ritonavir were only slightly above the target upper limit and the median tenofovir AUC and C max were similar to what is described for patients not receiving concurrent atazanavir and ritonavir (6). However, tenofovir AUC and C min were higher than those reported in 22 HIV-infected young adults Ն18 to Ͻ25 years of age who received concomitant atazanavir and ritonavir (9). The authors suggested that the lower tenofovir exposure seen in their adolescent population may be due to faster tenofovir clearance (49.2 liters/h).…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast, we found that the GMs (90% CI) for tenofovir AUC and C min in the presence of atazanavir-ritonavir were only slightly above the target upper limit and the median tenofovir AUC and C max were similar to what is described for patients not receiving concurrent atazanavir and ritonavir (6). However, tenofovir AUC and C min were higher than those reported in 22 HIV-infected young adults Ն18 to Ͻ25 years of age who received concomitant atazanavir and ritonavir (9). The authors suggested that the lower tenofovir exposure seen in their adolescent population may be due to faster tenofovir clearance (49.2 liters/h).…”
Section: Discussioncontrasting
confidence: 43%
“…In previous TDF-FPV/RTV coadministration studies, the effect of adding an FPV regimen to a TDF regimen was not evaluated. However, two studies that evaluated APV pharmacokinetics following the addition of TDF 300 mg qd to an FPV/RTV 700/100 mg bid or 1400/200 mg qd regimen noted negligible increases in steady-state APV APV and TFV pharmacokinetic changes observed in our study were unlikely to be clinically important because the steady-state geometric mean TFV C min remained within the range reported in HIV-infected patients treated with TDF 300 mg qd without concurrent FPV [22][23][24], and the geometric mean APV C min for unboosted FPV (0.351 mg/ mL) and FPV/RTV (2.88 mg/mL) during TDF coadministration remained 2.4-and 19.7-fold higher than the documented protein binding-adjusted 50% inhibitory concentration (IC 50 ) for wild-type HIV isolates (0.146 mg/mL), respectively [25].The pattern of plasma C min and AUC changes that we observed during TDF-FPV and TDF-FPV/RTV coadministration was different from the pattern reported when TDF was given with ATV [10,26], ATV/RTV [10,11,27], LPV/RTV [12,13,24,28] or indinavir (IDV) [13] (increase in TFV and decrease in PI), DRV or brecanavir (BCV) (increase in TFV and PI) [14,29], nelfinavir (NFV) (no change in TFV and decrease/no change in NFV and/or active metabolite M8) [30,31], saquinavir (SQV) (increase in TFV and increase/no change in SQV) [22,32], or TPV/RTV (no change/increase in TFV and decrease in TPV) [33]. Interactions between TDF and PIs can potentially occur at the kidney and/or the gut level.…”
mentioning
confidence: 57%
“…However, two studies that evaluated APV pharmacokinetics following the addition of TDF 300 mg qd to an FPV/RTV 700/100 mg bid or 1400/200 mg qd regimen noted negligible increases in steady-state APV C min values (by 4% [15] and 2% [19], respectively). The Fosamprenavir-tenofovir interaction 195 APV and TFV pharmacokinetic changes observed in our study were unlikely to be clinically important because the steady-state geometric mean TFV C min remained within the range reported in HIV-infected patients treated with TDF 300 mg qd without concurrent FPV [22][23][24], and the geometric mean APV C min for unboosted FPV (0.351 mg/ mL) and FPV/RTV (2.88 mg/mL) during TDF coadministration remained 2.4-and 19.7-fold higher than the documented protein binding-adjusted 50% inhibitory concentration (IC 50 ) for wild-type HIV isolates (0.146 mg/mL), respectively [25].…”
Section: Discussionmentioning
confidence: 81%
“…Profiles of TFV in plasma and TFV/TFV-DP in PBMCs. Figure 3 displays for fetuses and neonates the observed and predicted TFV concentrations in plasma, TFV concentrations in PBMCs, and TFV-DP concentrations in PBMCs as a function of time in our study and the plasma TFV and TFV-DP concentrations reported in previous studies of adults (15,17,19,20). Fetal and neonatal plasma TFV and IC TFV-DP concentrations were compared to adult values measured in the same laboratory with the same method of dosage (20,21).…”
Section: Validationmentioning
confidence: 99%